3D computational fluid dynamics simulation of a 3-fluid liquid-to-air membrane energy exchanger (LAMEE). (5th May 2019) - Rashidzadeh, Masoud; Pourmahmoud, Nader; Simonson, Carey J.
Highlights: Conjugate heat and moisture transfer of a 3-fluid LAMEE is explored. Entered water vapor to desiccant solution changes to liquid and dilutes it. Refrigeration tubes cool down desiccant solution according to their locations. Lower tubes have to cool hotter desiccant solution rather than upper tubes. Upper layers of air flow lose higher values of moisture and heat. Abstract: In this article, a 3-fluid liquid-to-air membrane energy exchanger (LAMEE) prototype has been modeled using 3D computational fluid dynamics (CFD) technique. Applying advanced CFD simulation along with UDF (User Defined Function) and UDS (User Defined Scalar) external computer programs are major efforts of the present study which have overcome some computational restrictions of conventional numerical simulation software. Therefore, additional equations of mass and energy transfer are accompanied with fundamental governing equations of Newtonian fluid flow to explore the complexity of numerical analysis. The rates of conjugate heat and moisture transfer through the membrane, air and desiccant exit temperatures and the cooling effect of the refrigeration tubes are evaluated and shown in detail. The calculated temperature and humidity ratio at the outlet of the 3-fluid LAMEE agree well with available experimental data. The present CFD simulation reveals the diverse cooling effect of the different refrigeration tubes in the 3-fluid LAME depending on their individual geometrical location. The refrigeration tubes increase the sensible, latent and total effectiveness, moisture removal rate and sensible cooling capacity 72%, 29%, 41%, 13.0 gv /h and 8.7 W, respectively. The obtained temperature and humidity ratio contours and flow patterns throughout the 3-fluid LAMEE reveal the mechanisms of dehumidification, cooling and phase change.